A Drosophila SNAP-25 null mutant reveals context-dependent redundancy with SNAP-24 in neurotransmission. - Vilinsky, I.; Stewart, B.A.; Drummond, J.; Robinson, I.; Deitcher, D.L. (Genetics, 2002)
The synaptic protein SNAP-25 is an important component of the neurotransmitter release machinery, although its precise function is still unknown. Genetic analysis of other synaptic proteins has yielded valuable information on their role in synaptic transmission. In this study, we performed a mutagenesis screen to identify new SNAP-25 alleles that fail to complement our previously isolated recessive temperature-sensitive allele of SNAP-25, SNAP-25(ts). In a screen of 100,000 flies, 26 F(1) progeny failed to complement SNAP-25(ts) and 21 of these were found to be null alleles of SNAP-25. These null alleles die at the pharate adult stage and electroretinogram recordings of these animals reveal that synaptic transmission is blocked. At the third instar larval stage, SNAP-25 nulls exhibit nearly normal neurotransmitter release at the neuromuscular junction. This is surprising since SNAP-25(ts) larvae exhibit a much stronger synaptic phenotype. Our evidence indicates that a related protein, SNAP-24, can substitute for SNAP-25 at the larval stage in SNAP-25 nulls. However, if a wild-type or mutant form of SNAP-25 is present, then SNAP-24 does not appear to take part in neurotransmitter release at the larval NMJ. These results suggest that the apparent redundancy between SNAP-25 and SNAP-24 is due to inappropriate genetic substitution.